The Functional Efficacy of A Solution-Focused Brief Therapy (SFBT)-Based Supervisory Program In Developing Active Listening And Crisis Intervention Skills Among Counselors In Governmental Schools Within The Salfit Governorate, Palestine. (Journal of the College of Basic Education, 2026)
This study aims to determine the functional efficacy of a Solution-Focused Brief Therapy (SFBT)-based supervisory program in developing Active Listening and Crisis Intervention skills among counselors in governmental schools within the Salfit Governorate, Palestine.The research utilizes a Single-Case Design (SCD) of the A-B type. The sample includes a single counselor (N=1) practicing in the Salfit Governorate. Data collection is conducted using an objective performance observation card administered over a total of ten (10) repeated measurement sessions.The findings reveal the achievement of an ideal effect size (U = 1.00) for both Listening and Intervention skills. This unequivocally establishes a functional relationship and demonstrates the program's exceptional efficiency in achieving an immediate performance improvement.Based on this demonstrated efficacy, the study recommends integrating the Solution-Focused supervision model into intensive training programs for developing the essential functional skills of school counselors.This study aims to determine the functional efficacy of a Solution-Focused Brief Therapy (SFBT)-based supervisory program in developing Active Listening and Crisis Intervention skills among counselors in governmental schools within the Salfit Governorate, Palestine.The research utilizes a Single-Case Design (SCD) of the A-B type. The sample includes a single counselor (N=1) practicing in the Salfit Governorate. Data collection is conducted using an objective performance observation card administered over a total of ten (10) repeated measurement sessions.The findings reveal the achievement of an ideal effect size (U = 1.00) for both Listening and Intervention skills. This unequivocally establishes a functional relationship and demonstrates the program's exceptional efficiency in achieving an immediate performance improvement.Based on this demonstrated efficacy, the study recommends integrating the Solution-Focused supervision model into intensive training programs for developing the essential functional skills of school counselors.